SOCIOECONOMIC ANALYSIS OF RURAL COMMUNITY FAZENDA DO POVO, IPIAÚ MUNICIPALITY, BAHIA, BRAZIL - Bruno-Lima, Nelma (2016)
The main objective of this research was to analyze the socioeconomic reality of the Rural Community Fazenda do Povo of Ipiaú, Bahia, in regards to municipal and regional socio-economy. Therefore, socioeconomic indicators in the region, the city of Ipiaú, and the community were analyzed. The results showed a positive situation of the community regarding schooling, compared to the reality of other settlements of agrarian reform; the issue of income and per capita income; the low dependence on government social benefits; and job covering. Besides, they showed how negative the high frequency of agrochemicals used in the management of production is.